2013
DOI: 10.1016/j.jhep.2013.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Decoding cell death signals in liver inflammation

Abstract: Inflammation can be either beneficial or detrimental to the liver, depending on multiple factors. Mild (i.e., limited in intensity and destined to resolve) inflammatory responses have indeed been shown to exert consistent hepatoprotective effects, contributing to tissue repair and promoting the re-establishment of homeostasis. Conversely, excessive (i.e., disproportionate in intensity and permanent) inflammation may induce a massive loss of hepatocytes and hence exacerbate the severity of various hepatic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
583
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 799 publications
(602 citation statements)
references
References 164 publications
13
583
0
6
Order By: Relevance
“…Mechanism can be inferred from enriched GO terms, for example, hypertrophy and 'glutathione metabolic process' for module 42m or single-cell necrosis and 'MAPK signaling' for module 29 (Table 1). Modules 70 (enriched with cell cycle arrest genes, including Ddit3) and 29 (enriched for MAPK signaling consistent with apoptosis processes in liver 27 ) were associated with single-cell necrosis, but not with necrosis (non-programmed cell death; single-cell necrosis is synonymous with programmed cell death or apoptosis in histological evaluation 28 ). Thus, clustering on p-adj revealed distinct module associations with distinct forms of cell death not observed when clustering on effect size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism can be inferred from enriched GO terms, for example, hypertrophy and 'glutathione metabolic process' for module 42m or single-cell necrosis and 'MAPK signaling' for module 29 (Table 1). Modules 70 (enriched with cell cycle arrest genes, including Ddit3) and 29 (enriched for MAPK signaling consistent with apoptosis processes in liver 27 ) were associated with single-cell necrosis, but not with necrosis (non-programmed cell death; single-cell necrosis is synonymous with programmed cell death or apoptosis in histological evaluation 28 ). Thus, clustering on p-adj revealed distinct module associations with distinct forms of cell death not observed when clustering on effect size.…”
Section: Resultsmentioning
confidence: 99%
“…Jun, associated with immediate early response module 29, and Jun kinase (JNK) play important roles in liver pathogenesis. 27,54 Fxr and Hnf1a are implicated broadly in cholestatic liver injury. [55][56][57][58] Reports that Sp1 plays a role in liver injury are more anecdotal.…”
Section: Resultsmentioning
confidence: 99%
“…2 Subsequent studies by us and others identified various mechanisms that underlie not only the ability of a specific stimulus to trigger bona fide ICD as opposed to a non-immunogenic instance of apoptosis, but also the capacity of the host to detect ICD and hence mount a therapeutically relevant immune response against dying cells. 1, [3][4][5][6] Schematically, ICD itself relies on the coordinated emission of a series of damage-associated molecular patterns (DAMPs), [7][8][9][10][11][12] including the exposure of endoplasmic reticulum (ER) chaperones on the cell surface, the secretion of ATP and the release of the non-histone chromatin-binding protein high mobility group box 1 (HMGB1), [13][14][15][16][17][18][19][20] and immunostimulatory cytokines, such as type I interferons. 21 When emitted in the correct spatiotemporal pattern, [22][23][24] such DAMPs recruit antigen-presenting cells, including dendritic cells, to the site of ICD and activate them to engulf dead cell-associated antigens, process and present them to CD4 C and CD8 C T lymphocytes in the context of co-stimulatory signals, resulting in the priming of a robust, antigen-specific immune response.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] So far, only a few stimuli have been ascribed with the ability to trigger ICD, encompassing both chemical and physical agents. 3,36 Interestingly, such bona fide ICD inducers include various anticancer chemotherapeutics that have been successfully employed in the clinic for several years (Table 1), like (1) doxorubicin, an anthracycline approved by the US Food and Drug Administration (FDA) for the treatment of acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), breast carcinoma, gastric cancer, lymphoma, multiple myeloma (MM), neuroblastoma, ovarian carcinoma, small cell lung carcinoma, soft tissue and bone sarcomas, thyroid carcinoma, transitional cell bladder carcinoma and Wilms' tumor; 2,49 (2) epirubicin, an anthracycline licensed for use in breast carcinoma patients; 2,49 (3) idarubicin, an anthracycline currently employed for the treatment of AML; 19,49 (4) mitoxantrone, an anthracenedione licensed for use in individuals with AML, breast carcinoma, nonHodgkin's lymphoma (NHL) and prostate carcinoma; 2,49 (5) bleomycin, a glycopeptide antibiotic commonly employed as a palliative treatment for Hodgkin's lymphoma, NHL, penile cancer, testicular cancer, and squamous carcinomas of the head and neck, cervix and vulva; 50 (6) bortezomib, a proteasomal inhibitor approved for use in subjects with MM and mantle cell lymphoma; 17,51,52 (7) cyclophosphamide, an alkylating agent nowadays employed for the treatment of ALL, AML, chronic lymphocytic leukemia, breast carcinoma, chronic myeloid leukemia (CML), lymphoma, MM, mycosis fungoides, neuroblastoma, ovarian carcinoma and retinoblastoma; 53 and (8) oxaliplatin, a platinum derivative approved for use in combination with 5-fluorouracil and folinic acid for the therapy of advanced colorectal carcinoma. 40,44,54 Moreover, at least in some cell types, ICD can be provoked by patupilone, an experimental microtubular inhibitor of the epothilone family, [55][56][57] and by 7A7, a monoclonal antibody (mAb) targeting the murine epidermal growth factor receptor (EGFR).…”
Section: Introductionmentioning
confidence: 99%
“…Among this abundant literature, we found of especial interest the works of (1) Arulanandam and colleagues (Ottawa Hospital Research Institute, Ottawa, Canada), who discovered that a transcriptional modulator operating downstream of vascular endothelial growth factor receptors (VEGFRs) 208,209 suppresses Type I interferon (IFN) responses, 210 hence sensitizing the tumor vasculature to infection by oncolytic viruses, 211 and found that microtubule-destabilizing agents commonly employed in the clinic (e.g., paclitaxel) 212,213 synergize with oncolytic virotherapy by disrupting the translation of Type I IFN-coding mRNAs and by exacerbating the demise of cancer cells provoked by the cytopathic effect; 214 (2) Nishio and collaborators (Baylor College of Medicine, Houston, TX, US), who reported that an oncolytic adenovirus genetically engineered to express interleukin-15 (IL-15) and chemokine (C-C motif) ligand 5 (CCL5, also known as RANTES) improved the therapeutic potential of adoptively transferred T cells expressing a chimeric antigen receptor (CAR) 215,216 [218][219][220][221][222] a means to boost the replication (and hence the efficacy) of an oncolytic HSV-1 strain; 223 (4) Parrish and co-authors (St James's University Hospital, Leeds, UK), who discovered that an oncolytic reovirus enhances the capacity of the FDA-approved CD20-targeting monoclonal antibody rituximab 224,225 to stimulate antibody-dependent cellular cytotoxicity; 226 , who discovered that autonomous parvoviruses are endowed with a rather advantageous feature for the development of novel oncolytic virotherapies, namely, they neither trigger nor inhibit Type I IFN responses in normal and malignant cells; 236 (11) Zloza and coauthors (Rush University Medical Center, Chicago, IL, US), who suggested that the downregulation of leukocyte immunoglobulin-like receptor, subfamily B (with TM and ITIM domains), member 1 (LILRB1, also known as ILT2) in peripheral blood mononuclear cells may constitute a reliable biomarker of therapeutic responses to oncolytic virotherapy in cancer patients; 237 (12) Liikanen and colleagues (University of Helsinki, Helsinki, Finland), who propose that the circulating levels of the damage-associated molecular pattern high mobility group box 1 (HMGB1) [238][239][240][241] at baseline may constitute a robust prognostic factor as well as a predictive indicator of disease control up...…”
Section: Preclinical and Translational Advancesmentioning
confidence: 99%